Sonothrombolysis: State-of-the-Art and Potential Applications in Children - Rebecca E. Ward; Santiago Martinez-Correa; Luis Octavio Tierradentro-García; Misun Hwang; Chandra M. Sehgal (MDPI AG, 2023)
In recent years, advances in ultrasound therapeutics have been implemented into treatment algorithms for the adult population; however, the use of therapeutic ultrasound in the pediatric population still needs to be further elucidated. In order to better characterize the utilization and practicality of sonothrombolysis in the juvenile population, the authors conducted a literature review of current pediatric research in therapeutic ultrasound. The PubMed database was used to search for all clinical and preclinical studies detailing the use and applications of sonothrombolysis, with a focus on the pediatric population. As illustrated by various review articles, case studies, and original research, sonothrombolysis demonstrates efficacy and safety in clot dissolution in vitro and in animal studies, particularly when combined with microbubbles, with potential applications in conditions such as deep venous thrombosis, peripheral vascular disease, ischemic stroke, myocardial infarction, and pulmonary embolism. Although there is limited literature on the use of therapeutic ultrasound in children, mainly due to the lower prevalence of thrombotic events, sonothrombolysis shows potential as a noninvasive thrombolytic treatment. However, more pediatric sonothrombolysis research needs to be conducted to quantify the safety and ethical considerations specific to this vulnerable population.